Aktifitas Tabir Surya Dengan Nilai Sun Protection Factor (SPF) Sediaan Losion Kombinasi Ekstrak Kayu Manis Dan Ekstrak Kulit Delima Pada Paparan Sinar Matahari Dan Ruang Tertutup - Youstiana Dwi Rusita; Indarto A.S (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract : SPF, Kayumanis, Pomegranate, Lotions. The Sun produces ultraviolet radiation that causes damage to the skin texture, premature aging, burning skinreactions and skin cancer in exposed skin in a long period. One of the ways to protect skin from UV radiation use sunscreen lotions. Stem bark of cinnamon (Cinnamomun burmani) and pomegranate peel (Punica granatum) is known as an antioxidant activity and have a compound that is potentially as sunscreens. This research aims to know the activity of sunscreen with an SPF value of sunscreen lotions of pomegranate peel and cinnamon extract and the warming rays of the Sun and closed space. The determination of the value of the sun protection factor is done with methods of in vitro in Mansur using spectrophotometer UV-Vis. SPF Value calculated based on the Absorbance at a wavelength of 290-320 nm. The result is a non parametric Test is analyzed using MannWhitney test. Results of organoleptic the colored is yellow brown, like to emultion and shaped the distinctive, smell of cinnamon, less homogeneous, showed the value of pH5.63, dispersive power 6 cm, adhesion 1.75 seconds and viscosity 5,500 cps. Preparations that are exposed in the Sunlight showed the value of SPF 20.146 hereaspreparations stored in enclosed space showed the value of SPF 26.398. The results of statistical tests indicate that there is no difference between the SPF on reparations that are exposed to sunlight and in a closed space with alpha value > 0.05.